Sovereignty over Khor Abdullah in light of British Documents 1905-1940 - Karoon Freeh, Lect . Dr. Wijdan (Basra studies journal, 2025)
Khor Abdullah has been one of the most internationally disputed issues between Iraq and Kuwait since the 1990s. Due to its political, Geopolitics, economic, and historical significance. This study focuses on determining the ownership and sovereignty over the khor based on British correspondence between residents and political agents in the Arabian Gulf, the Government of India, and the British Foreign Office, along with their affiliated departments, during the period from 1905 to 1940, a timeframe defined by documents from the British archives in London. The documentary study revealed that sovereignty over Khor Abdullah went through two distinct phases, with World War I (1914-1918) serving as the dividing line between them. Given its influence in the Arabian Gulf, the British government held decisive authority, acting in accordance with its interests and pursuit of regional stability. The issue of the maritime boundary between Iraq and Kuwait remained unresolved and was repeatedly exploited by Britain as a means of exerting pressure on either country whenever it served its strategic objectives.